High‐salt diet increases hormonal sensitivity in skin pre‐capillary resistance vessels. (10th January 2013) - Helle, F.; Karlsen, T. V.; Tenstad, O.; Titze, J.; Wiig, H.
Abstract Aims Recent data indicate that the skin of rats on a high‐salt diet is able to accumulate Na+ without commensurate water. This extrarenal mechanism of Na+ homoeostasis could affect skin vasoregulation. We hypothesized that the major resistance vessel of rat skin, the pre‐capillary arterioles, has increased vasoreactivity within the physiological range of circulating ANG II, a hormone relevant to salt‐sensitive hypertension. Methods and results Skin arterioles from skin and muscle were isolated using the agar‐infusion technique. Vessels from rats fed high‐salt and low‐salt diet had similar lumen diameter and media area/lumen area ratio. Contractile sensitivity to ANG II was increased in skin vessels from high‐salt vessels at all doses tested starting at 10−10 m (P < 0.01). Pre‐capillary arterioles from muscle displayed similar contractions to ANG II, independent of the diet. As ANG II and the renin–angiotensin system are strongly involved in salt conservation, we explored whether vasoreactivity for noradrenaline was increased as well, because this is a functionally unrelated hormone. At low doses, contractions were similar, but at 10−5 and 10−4 m, noradrenaline produced stronger contractions in skin vessels from high‐salt compared with low‐salt rats (P < 0.01). Conclusions Our data demonstrate significantly increased hormonal vasoreactivity of skin vessels from rats on a high‐salt diet, which could increase peripheral resistance in many situations and contribute to higher pressure in salt‐sensitive hypertension. As vessels from adjacent muscle were unaffected, we raise the interesting possibility that increased vasoreactivity in the skin could be linked to osmotically inactive Na+ accumulation.